Modified SHA-1 Algorithm - Rogel Ladia Quilala; Ariel M Sison; Ruji P Medina (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Hashes are used to check the integrity of data. This paper modified SHA-1 by incorporating mixing method in every round for better diffusion. The modification increased the hash output to 192-bits. Increasing the output increases the strength because breaking the hash takes longer. Based on the different message types, avalanche percentage of modified SHA-1 showed better diffusion at 51.64%, higher than the target 50%, while SHA-1 achieved 46.61%. The average execution time noted for modified SHA-1 is 0.33 seconds while SHA-1 is 0.08 seconds. Time increases as the number of messages hashed increases; the difference is negligible in fewer messages. On character hits, that is - no same character in the same position, modified SHA-1 achieved lower hit rate because of the mixing method added. The modifications’ effectiveness was also evaluated using a hash test program. After inputting 1000 hashes from random strings, the result shows no duplicate hash.